The COVID-19 Pandemic: Global Impacts on Families - Charton, Laurence; Labrecque, Léoni; Lévy, Joseph Josy (Enfances, Familles, Générations, 2022)
Research Framework : The COVID-19 pandemic and the restrictive measures issued, such as physical distancing and lockdown, have affected social and family ties. These constraints have forced people to reexamine their family and conjugal relationship, the management of family and professional time, their intergenerational connections, and life transitions. Either exacerbating the tensions on conjugal and family life or strengthening these links, this pandemic has also provided an opportunity to explore on new strategies for living together. Objectives : This article offers an overview of the effects and consequences of the COVID-19 pandemic on families and their members. Methodology : This article is based on a literature review from various social science disciplines. Results : Partial insights were provided on the following questions: What effects did the pandemic have on families and family members? How did families manage the pandemic’s economic consequences? What were the repercussions of health measures that were put in place to counter the spread of COVID-19 on couples, children, intergenerational relationships, and mental health? How were mortuary rites and mourning processes affected? Conclusion : This article contributes, beyond the individual and social hardships resulting from COVID-19, to show familial – generational and community – solidarity and resiliency that have emerged, as well as the ways in which families and their members have coped and organized themselves during the pandemic. Contribution: Throughout history, societies have been confronted with epidemics that have affected all spheres of life. The COVID-19 pandemic has once again highlighted the importance, fragility and strength of the social and family ties, along with the challenges of living together.